WARM-UP BEFORE PHYSICAL EFFORT ̶ ITS NEED AND IMPORTANCE IN THE ACTIVITY OF MILITARY PHYSICAL TRAINING - Alin PELMUȘ (Bulletin of "Carol I" National Defense University, 2021)
After defining and presenting the types of warm-up, the article highlights the need and importance of performing such an action effectively before carrying out any type of physical effort and especially that specific to military activity. Throughout the article, it is emphasized that a well-planned warm-up, with a relevant content and in harmony with the specific objectives of the training or sports competition, substantially reduces the risk of injury and clearly improves motor performance. Also, the article includes in its final part a warm-up protocol that can be used successfully in the area of ​​military physical training, in which military instructors have the opportunity to develop diversified physical exercises, beneficial for achieving superior performance.